PENGARUH KETERAMPILAN PENGELOLAAN KELAS, METODE MENGAJAR GURU DAN KEAKTIFAN SISWA TERHADAP HASIL BELAJAR IPS TERPADU - Frederika Feni Fitri; Andriani Rosita; Rusno Rusno (Fakultas Ekonomika dan Bisnis, Universitas Kanjuruhan Malang, 2017)
This research aims to know: 1) The Influence of Management Classroom Skill, Methods of Teaching Teacher, and Student Activity to Social Studies Learning Result, 2) The Influence of Management Classroom Skill to Social Studies Learning Result, 3) Methods of Teaching Teacher to Social Studies Learning Result, 4) Student Activity to Social Studies Learning Result. The kind of research is explanatory research. The population is all student class VII dan VIII in SMP Kristen Petra Malang as many as 59 students. Data collection was stiffened by using quetionnaires and documentation. Data technique analysis uses multiple linear regression analysis. The result of this research show: 1) The Management Classroom Skill, Methods of Teaching Teacher, and Student Activity have significant influence to social studies learning result of student with value Fcount for 16.868 with significant value 0,000<0,05 and R2 value is 0,479. 2) The Influence of Management Classroom Skill have significant influence to social studies learning result of student with value Fcount for 2.639 with significant value 0,011<0,05. 3) Methods of Teaching Teacher have significant influence to social studies learning result of student with value Fcount for 2.927 with significant value 0,005<0,05. 4) Student Activity have significant influence to social studies learning result of student with value Fcount for 2.085 with significant value 0,003<0,05.